Filamentous cyanobacteria from western ghats of North Kerala, India (Bangladesh Journal of Plant Taxonomy, 2021)
Cyanobacteria are Gram negative, photosynthetic and nitrogen fixing microorganisms which contribute much to our present-day life as medicines, foods, biofuels and biofertilizers. Western Ghats are the hotspots of biodiversity with rich combination of microbial flora including cyanobacteria. Though cosmopolitan in distribution, their abundance in tropical forests are not fully exploited. To fill up this knowledge gap, the present research was carried out on the cyanobacterial flora of Peruvannamuzhi forest and Janaki forests of Western Ghats in Kozhikode District, North Kerala State, India. Extensive specimen collections were conducted during South-West monsoon (June to September) and North-East monsoon (October to December) in the year 2019. The highest diversity of cyanobacteria was found on rock surfaces. A total of 18 cyanobacterial taxa were identified. Among them filamentous heterocystous forms showed maximum diversity with 10 species followed by non- heterocystous forms with 8 species. The highest number of cyanobacteria were identified from Peruvannamuzhi forest with 15 taxa followed by Janaki forest with 3 taxa. The non- heterocystous cyanobacterial genus Oscillatoria Voucher ex Gomont showed maximum abundance with 4 species. In this study we reported Planktothrix planktonica (Elenkin) Agagnostidis & Komárek 1988, Oscillatoria euboeica Anagnostidis 2001 and Nostoc interbryum Sant’Anna et al. 2007 as three new records from India.Bangladesh J. Plant Taxon. 28(1): 83-95, 2021 (June)